Analysis of E-Library Based on Level of User Satisfaction Using EUCS and IPA Methods - Muhammad Luthfi Hamzah; Lovi Anisa Hultari; Astri Ayu Purwati; Nazaruddin Nazaruddin (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2022)
technology, namely the use of e-Library as an online catalog facility to directly access collections of books, theses or other collections contained in the library. This research is based on the fact that users feel dissatisfied with the services provided by the e-Library, such as collections and collection information that do not meet user needs. The purpose of this study was to measure the level of satisfaction of e-Library users using the End User Computing Satisfaction method with five perspectives namely Content, Accuracy, Format, Ease of Use, and Timeliness. The Impotance Performance Analysis (IPA) method is used to determine which attributes are important to be improved and which need to be reduced to be interpreted in the form of a matrix. This study also calculates the value of Customer Satisfaction Index (CSI) to determine the overall level of user satisfaction. The results of this study show that all attributes in terms of Importance are in a very important category, while the Performance attributes are in the satisfied category, namely the Content and Format variables. Variables with quite satisfied categories on Accuracy, Ease of Use and Timeliness variables. The results of the IPA matrix obtained 6 attributes with the most improvement in the Accuracy variable, the attribute with the most good performance in the Content variable. Overall, the CSI value is 60.34%, which means that users are quite satisfied with the performance provided by the e-Library